UMKM JAKARTA NAIK KELAS: PERAN MANAJEMEN BISNIS DALAM BERSAING DI PASAR LOKAL & GLOBAL - Deny Sudrajat; Ermanuri, Ermanuri; D Purnomo; Aris Hendrawan; Muhammad Azhar Nasution (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the role of business management in encouraging Micro, Small, and Medium Enterprises (MSMEs) in Jakarta and its surrounding areas to move up to a higher level and enhance their competitiveness in local and global markets. The study employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to 100 MSME owners in Jakarta and surrounding areas. The variables measured include business management practices—covering financial management, marketing, production, and human resource management—and MSME competitiveness. Data were analyzed using descriptive statistics and simple linear regression analysis. The results indicate that business management has a positive and significant effect on MSME competitiveness. MSMEs that apply more structured and integrated business management practices tend to experience increased revenue, market expansion, improved product quality, and higher levels of managerial professionalism. These findings highlight that the success of MSMEs in moving up to a higher level in urban areas is determined not only by the adoption of digital technology and online marketing, but also by strong managerial capabilities and adaptability to dynamic market competition.